Exports trade, employment and poverty reduction in Nigeria (2012)
Purpose – Poverty reduction remains one of the main goals of development efforts, as evidenced by the adoption of the Millennium Development Goals by most developing countries and international agencies. The purpose of this paper is to explore the relationship between trade (exports) and employment and how the relationship reduces poverty through the instrumentality of employment, with a focus on Nigeria. Design/methodology/approach – The paper takes the form of descriptive analysis. Findings – Evaluating the case for Nigeria, the authors find that oil exports which drives economic growth do not provide the needed employment to reduce poverty, while agricultural trade, particularly exports, are capable of reducing poverty and inequality in Nigeria through the channel of employment and agricultural productivity growth. Originality/value – The paper makes a link between export trade, employment and poverty reduction in Nigeria.